Seismic anisotropy time variations at Mt Etna. Issue 1 (11th October 2019) - Nardone, Lucia; Bianco, Francesca; Zaccarelli, Lucia; Patanè, Domenico
SUMMARY: The aim of this paper is to study the temporal variations in the seismic wavefield associated with the stress changes in the dynamic features of the Mt Etna volcanic activity. We used shear wave splitting analysis on a huge data set of local earthquakes, in order to identify changes of the local stress field at Mt Etna during the time interval from 2006 to 2011. This analysis allows us to obtain two parameters: the polarization direction of the fast shear wave (φ) and the time delay of the slow shear wave ( T d, time delay between the split shear waves). Orientation of φ generally provides information about the anisotropic symmetry and stress direction whereas T d provide information about the average crack density along the ray path. Based on our findings it is possible to divide Etna Volcano in three different sectors, each one distinguished by typical fast wave polarization direction. We find that the western part of the volcano is controlled by the regional tectonic stress field having a NS and EW directions. Instead, the eastern part of the volcano is mainly controlled by the local volcanic stress, particularly an EW local stress field in the NE sector (Pernicana), and a quasi NS local stress field in the SE sector (Mascalucia, Timpe), where previous studies evidenced: (i) some low-Qp anomaly regions between 0 and about 6 km depth, probably associated with high pore pressure and the intense faulting and (ii) by magnetotelluric surveys, several high conductivity zones, up to 8 km depth, related to a diffuse presence of hydrothermal activity and fluid circulation. Temporal variations in time delay, mostly before the 2008–2009 lateral eruption, can be interpreted as stress accumulation increase with a consequent release of stress due to coalescing of microcracks in the conduit for the eruption of magma.